Analysis of morphological, microstructural, electrochemical and nano mechanical characteristics of TiCN coatings prepared under N2 gas flow rate by chemical vapour deposition (CVD) process at higher temperature. Issue 8 (1st June 2020) - Das, Soham; Guha, Spandan; Das, Partha Protim; Ghadai, Ranjan K.
Abstract: In the present study, Titanium carbon nitride (TiCN) thin films have been synthesized over Si (100) substrate using chemical vapour deposition (CVD) process under N2 gas flow rate to study the suitability of CVD for the growth of TiCN coating over machine tools. The morphological, structural, corrosion behavior and mechanical properties of the coatings have been characterized using a scanning electron microscope (SEM), atomic force microscopy (AFM), x-ray diffraction (XRD), corrosion test and Nano-indentation. SEM images revealed a smoother morphology of the TiCN coating surface without any pores. The AFM results revealed an increase in surface roughness from 40.88 nm to 48.25 nm. The particle size of TiCN thin film also found to be increasing with a higher N2 flow rate. The XRD peaks of TiCN were observed in the range of 37°-38°. 44°-44.5° and 61°- 62° attributed to (111), (200) and (220) crystal plane. The XRD results also confirmed the presence of stress in the coatings. The polarization test indicates a reduction of corrosion resistance with a higher N2 gas flow rate. The mechanical properties investigated by the nano-indentation method indicated an increase in Hardness (H) and Young's modulus (E) of the coating with a higher N2 flow rate. The maximum H and E of the coatings were observed as 27.85 GPa and 486.22 GPa respectively.